Kemampuan Mengenali Emosi pada Anak Sekolah Dasar sebagai Landasan bagi Perkembangan Sosial-Emosional: Perspektif Fenomenologis dari Dusun Benyo: Penelitian - Anifa Tuzzuhroh Nurbaiti; Titis Nurhidayati (Jurnal Pustaka Cendekia Pendidikan, 2026)
The ability to recognize emotional expressions is a crucial aspect of the social and emotional development of elementary school-aged children. This study aims to understand the experiences of 10–12-year-old children in Benyo Hamlet in recognizing and interpreting various emotional expressions in everyday life. The study used a qualitative approach with an interpretative phenomenological analysis (IPA) design. Participants were selected purposively until data saturation reached. The results showed that most children were able to recognize basic emotions such as happiness, sadness, and anger well. However, they still had difficulty distinguishing more complex emotions, such as shame, disappointment, anxiety, and confusion. The family environment and rural culture play an important role in developing children's understanding and managing emotions. In addition, the use of visual media in the form of emotion boards helped children express their emotional experiences more easily. These findings suggest that the ability to recognize emotions develops gradually and is influenced by social interactions, family communication patterns, and the cultural context in which children grow up.